Urban Dynamics of Nakhon Chai Si and Leadership for Sustainability - Boonyim , Vorachai; Kangsadanporn, Korn (Journal of Dhamma for Life, 2026)
The objectives of this study are: (1) to examine the perspectives of local leaders, residents, and stakeholders regarding the dynamic transformations of Nakhon Chai Si Municipality across the economic, social, political-administrative, and environmental dimensions; (2) to analyze the roles of leadership, local administrative mechanisms, and social capital in shaping the city’s development trajectory; and (3) to synthesize preliminary opportunities, constraints, and policy directions for advancing Nakhon Chai Si toward sustainable urban development. This research employs a qualitative methodology, collecting data through in-depth interviews, focus group discussions, and field observations. Data were analyzed using thematic analysis, and the credibility of the findings was enhanced through triangulation across multiple data sources. The results indicate that Nakhon Chai Si is undergoing pronounced transformations in four major dimensions: the expansion of service sectors and emerging businesses alongside the decline of agricultural land; growing social diversity and tensions between traditional community lifestyles and emerging urban cultures; limitations in policy continuity and citizen participation; and heightened environmental risks stemming from shifting land-use patterns. The analysis highlights that visionary leadership—characterized by systems thinking, strong communication skills, and the ability to coordinate across sectors—plays a crucial role in strengthening the city’s capacity to navigate these complex dynamics. At the same time, forms of social capital such as trust, community networks, and cross-sector collaboration serve as supportive mechanisms that help mitigate conflicts and enhance the city’s potential to manage change sustainably.